2013
DOI: 10.3109/13651501.2013.777744
|View full text |Cite
|
Sign up to set email alerts
|

Remission of obsessive-compulsive disorders and syndromes; evidence from a prospective community cohort study over 30 years

Abstract: Our findings suggest a lack of diagnostic stability over the long-term and a high chance of eventual remission, albeit often after several years of illness, for obsessive-compulsive syndromes including OCD. However, roughly one-third of OCD cases do not remit by 50 years of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 37 publications
(38 reference statements)
1
30
0
2
Order By: Relevance
“…However, there were numerous confounds to the study by Tolin et al (2010), including a dearth of older adults in the study sample, a lack of verification of hoarding status, and no differentiation in the type of hoarding symptom (e.g., saving, difficulty discarding, or clutter). Most important, the course of symptoms was not waxing and waning as seen in the trajectory of other mental health disorders across the lifespan, such as in OCD (Fineberg et al, 2013;Ravizza, Maina, & Bogetto, 1997;Skoog & Skoog, 1999) and in mood disorders (Coryell, Endicott, & Keller, 1990;Coryell et al, 1994;Richards, 2011). However, this may also be the result of our use of retrospective instead of longitudinal analyses.…”
Section: Discussionmentioning
confidence: 91%
“…However, there were numerous confounds to the study by Tolin et al (2010), including a dearth of older adults in the study sample, a lack of verification of hoarding status, and no differentiation in the type of hoarding symptom (e.g., saving, difficulty discarding, or clutter). Most important, the course of symptoms was not waxing and waning as seen in the trajectory of other mental health disorders across the lifespan, such as in OCD (Fineberg et al, 2013;Ravizza, Maina, & Bogetto, 1997;Skoog & Skoog, 1999) and in mood disorders (Coryell, Endicott, & Keller, 1990;Coryell et al, 1994;Richards, 2011). However, this may also be the result of our use of retrospective instead of longitudinal analyses.…”
Section: Discussionmentioning
confidence: 91%
“…In OCD, most longitudinal studies have reported on clinical cohorts (3336), although one population-based longitudinal cohort study has been performed in adults (37), with follow-up periods ranging between 3 and 40 years. Some of these studies suggest that OCD has a relatively stable and chronic course, while others report more favorable outcomes with age (3336).…”
Section: Objectivesmentioning
confidence: 99%
“…However, a recent epidemiological study suggests that approximately 50% of community-based cases followed up for approximately 30 years appear to have achieved remission by the age of 50 years, noting that only a minority (40%) sought professional treatment for their OCD (Fineberg et al, 2013b). More severe illness and a longer duration of illness were both associated with a lower likelihood of remission, highlighting the importance of early detection and treatment (Marcks et al, 2011;Eisen et al, 2013;Fineberg et al, 2013b). In the recent, prospective longitudinal study by Eisen et al (2013), participants with primary obsessions were more likely to experience a remission, whereas those with primary hoarding were less likely to remit, and over half of the participants who remitted subsequently relapsed.…”
Section: Relapse Prevention (Continuation and Maintenance Treatment)mentioning
confidence: 95%